Eksplorasi Penerapan Problem Based Learning dalam Mendorong Berfikir Kritis Siswa pada Pembelajaran Matematika Sekolah Dasar - Nurul Aulia; Riza Rahmatin; Afiah Zahra; Firdah Nailil Karimah (TARBAWIYAT, 2026)
This study aims to explore the application of Problem-Based Learning (PBL) in fostering critical thinking skills in elementary school students. The research approach used was qualitative with a descriptive approach. Data were collected through learning observations, interviews with teachers and students, and documentation of classroom activities. Data analysis was conducted through interactive data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of PBL in the classroom proceeds through the stages of contextual problem formulation, group discussions, information seeking, and solution presentation. This process creates an active, collaborative, and student-centered learning environment. Field findings also revealed that PBL can foster the development of students' critical thinking, as evidenced by their increased ability to identify problems, provide logical reasoning, ask questions, and evaluate their solutions. This study confirms that PBL has strong potential as an effective learning strategy in developing elementary school students' critical thinking skills, while also providing implications for teachers to continue optimizing problem-based learning in daily classroom practice.